Mobile Phone Security and Forensics A Practical Approach - Androulidakis, I.I (SpringerBriefs in Electrical and Computer Engineering, 2012)
Mobile Phone Security and Forensics provides both theoretical and practical background of security and forensics for mobile phones. The author discusses confidentiality, integrity, and availability threats in mobile telephones to provide background for the rest of the book. Security and secrets of mobile phones are discussed including software and hardware interception, fraud and other malicious techniques used "against" users. The purpose of this book is to raise user awareness in regards to security and privacy threats present in the use of mobile phones while readers will also learn where forensics data reside in the mobile phone and the network and how to conduct a relevant analysis.